Smart Vehicle Security System Using GSM & GPS (International Journal of Engineering and Computer Science, 2015)
The main motto of the project is to use the wireless technology effectively for the automotive environments by using the GSM Modem used in sending sms in case of theft intimation. The main scope of this project is to stop the engine of an automobile automatically. This can be done whenever a person trying to steal the vehicle, at that time sends an interrupt to a programmable microcontroller of 8051 family that stores owner's number upon a miss call for the first time. When someone tries to steal the car then microcontroller gets an interrupt and orders GSM Modem to send the sms, the owner receives a SMS that his car is being stolen then the owner sends back the SMS to the GSM modem to 'STOP', while the vehicle will be stopped. The control instruction is given to the microcontroller through interface, the output from which activates a relay driver to trip the relay that disconnects the ignition of the automobile resulting in stopping the vehicle.